The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1007/bf00442694
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor development in congenital hypothyroidism

Abstract: In 1979 a national screening programme for congenital hypothyroidism (CH) was introduced in Greece. Treatment with L-thyroxine was started immediately after confirmation of the diagnosis, at a median age of 28 days. A standardized development test (Griffiths) was given to a group of CH infants and to healthy controls at the ages of 5-7, 11-13, 17-19, and 23-25 months. Thirty-three infants with CH were also studied at the age of 35-37 months. The mean developmental quotient of CH infants was 103.8 +/- 12.0, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several studies (1-3) report CHT infants displaying minor neurologic dysfunctions and subnormal IQ at later age despite early diagnosis and treatment. Other studies report normal findings (4)(5)(6).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Several studies (1-3) report CHT infants displaying minor neurologic dysfunctions and subnormal IQ at later age despite early diagnosis and treatment. Other studies report normal findings (4)(5)(6).…”
mentioning
confidence: 86%
“…The importance of adequate induction is also supported by developmental studies in older CHT children. Normal IQ scores and normal school performances were obtained in those studies in which the patients received a high initial dosage of I-T4 (8 to 10 or 10 pg/kg/d) (4)(5)(6)29). In those studies in which a lower induction regimen was given comparable to that of our study (1-3), however, subnormal IQ scores and developmental delays were found, especially for the TD patients.…”
mentioning
confidence: 99%
“…The most important determinants for outcome are severity of hypothyroidism, defined by initial thyroxine level at the time of screening (Murphy et al 1990, Fuggle et al 1991, Derksen-Lubsen and Verkerk 1996, and age at the start of treatment (Ilicki andLarsson 1988, Rovet andEhrlich 2000). Although several studies assumed that early treatment might prevent irreversible impairment of brain development (Virtanen et al 1980, Ilicki and Larsson 1988, Komianou et al 1988, New England Congenital Hypothyroidism Collaborative 1990, there is ample evidence that neurological dysfunctions, motor disorders, and below normal IQ can persist but to a lesser degree (MacFaul et al 1978, Glorieux et al 1985, Rovet et al 1987. Early treatment by thyroxine replacement showed that vestibular function was similar to that in a control group (Meza et al 1996); delaying the onset of treatment was associated with poor outcome and led to abnormal vestibular function (Sato et al 1987).…”
mentioning
confidence: 99%